THE ADVANTAGES OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING FOREIGN LANGUAGE CULTURE - Ismailov Anvar Rustamovich (Sciental Journals Publishing, 2026)
The present article presents the analysis of the advantages of using modern pedagogical technologies in the process of teaching foreign language, speech etiquette in it, enriching vocabulary and developing speaking skills. The article demonstrates the most popular technologies used in teaching process.
Keywords: Pedagogical competence, speech etiquette, teaching process, pedagogical technologies, teaching effectiveness